A Panorama of Solidarity Economy in Santa Catarina, Brazil (Revista LIDER, 2017)
The Solidarity Economy theme has been gaining ground both in the academic sphere and in the agenda of the various actors. Not coincidentally, the aim of this study was to present a Solidarity Economy overview in the State of Santa Catarina, inserted in a contradictory socio-economic context: while, on one hand, the state has indicators that show a higher degree of development, on the other, it reveals significant disparities among their regions. To achieve this objective, the Solidarity Economy Atlas for the years 2007 and 2013 were examined. The questioning reveals that Santa Catarina’s development is marked by inequality and that the Solidarity Economy appears as an alternative for a significant portion of the population. By comparing the data in the observed period, it was evident that the Solidarity Economy practices have been strengthened over time, and they are not only an alternative to workers but also contribute to local and regional development. Moreover, such actions are configured as a space of selfmanagement practice and, therefore, of potential generalization of this behavior in society.